P191 Cerebellum and defensive behavior within the peripersonal space - Bocci, T.; Ferrucci, R.; Parenti, L.; Barloscio, D.; Vergari, M.; Cortese, F.; Priori, A.; Sartucci, F. (Clinical neurophysiology, 2017)
The cerebellum is involved in a wide number of integrative functions, ranging from working memory and associative learning to motor control; it also plays a role in the sensory-motor integration aimed at antinociceptive behavior, as well as in salience-related affective and behavioral responses to nociceptive stimulation. In healthy subjects we evaluated the role of cerebellum in defensive responses, as assessed with the so-called hand blink reflex (HBR), by modulating cerebellar activity with transcranial direct current stimulation (tDCS). TDCS was applied using a pair of electrodes with a surface area of 25cm2. The active electrode was centered on the median line 2cm below the inion, with its lateral borders about 1cm medially to the mastoid apophysis, and the return one over the right shoulder. Direct current was applied for 20min with an intensity of 1.5mA. For the recording of HBR, electrical stimuli were delivered using a surface bipolar electrode placed on the median nerve at the wrist and EMG activity was recorded from the orbicularis oculi muscle, bilaterally, using pairs of surface electrodes with the active electrode over the mid-lower eyelid and the reference electrode a few centimeters laterally to the outer canthus. Depending on the hand position respective to the face, we explored four different conditions: “hand far”, “hand near” (eyes open), “hand side”, “hand near” (eyes closed). EMG signals from each participant were high-pass filtered (55Hz), full-wave rectified, and averaged separately for the four conditions at the ipsilateral and contralateral recording sides. While anodal stimulation had no significant effect, cathodal one dramatically dampened the magnitude of the HBR, as measured by the area under the curve (AUC), when the stimulated hand was inside the peripersonal space surrounding the face at eyes closed (p<0.0001) or when it was placed laterally (p=0.004). Concurrently, HBR latency increased in both conditions “hand near” (eyes closed) and “hand side” (p=0.002 and 0.023, respectively). These results support a critical role of the cerebellum in the defensive responses within the peripersonal space, thus modulating defensive behavior even when the visuomotor feedback is lacking. [Display omitted]